Can the Cell-free DNA Test Predict Placenta Accreta Spectrum or Placenta Previa Totalis? - Adiyaman, Duygu; Kuyucu, Melda; Atakul, Bahar Konuralp; Can, Dilara; Özeren, Mehmet; Koç, Altuğ; Kutbay, Yaşar Bekir; Arıkan, Şener; Öztekin, Deniz (Zeitschrift für Geburtshilfe und Neonatologie, 2021)
Background Following the discovery that fetal DNA originates from the trophoblastic cells of the placenta, the contribution of the cell-free DNA test in placenta-related obstetric complications has begun to be investigated. Compared to uncomplicated pregnancies, higher fetal fractions were detected in placenta accreta spectrum and placenta previa, which are among placenta-related obstetric complications. However, this data applies only to advanced gestational weeks.Aim To investigate the possible predictive value of fetal fraction in cell-free DNA tests in pregnancies with placenta previa and placenta accreta spectrum in early gestational ages.Materials and Methods This study was conducted in women who were screened via cell-free DNA tests for common aneuploidies in the first and second trimester and subsequently diagnosed with placenta previa or placenta accreta spectrum. After the diagnosis was confirmed with a C-section, fetal fractions were retrospectively compared to a control group with a history of an uncomplicated C-section who were also previously screened by cell-free DNA test.Results The median and interquartile range (IQR) of fetal fractions for placenta previa (n=19), placenta accreta spectrum (n=7), and control groups (n=85) were 8.1 (6–10), 6.8 (6.7–10.7), and 7.1 (4.7–9.65), respectively. No statistically significant difference was observed among the three groups in terms of fetal fractions (p=0.587).Conclusions According to our data, we did not observe any relationship between placental invasion abnormalities vs. control group or placenta previa vs. control group using the fetal fractions of the cell-free DNA test. Furthermore, we could not confirm a predictive role and/or any additional clinical contribution. We believe that future studies focusing on placental mRNA might be more helpful than cell-free fetal DNA testing.
Keywords: cell-free DNA test; fetal fraction; placenta accreta spectrum; placenta previa